Anatomy as an Emerging Science and Career Option in View of Medical Students in Bangladesh - Chakraborty, Sanjoy Kumar; Hakim, Monjurul; Banu, Mst Laila Anjuman; Yousuf, BM Ali; Ali, M Shosher; Shamim, Kondkher Manzare (Bangladesh Journal of Anatomy, 2010)
Three hundred and thirty four medical students were questioned regarding their views on anatomy as an emerging science and further career option. A questionnaire with 16 statements was given to these students and their answers were compiled. The results of this study were encouraging. 99% of students consider anatomy as an essential pillar of medical science. A vast majority (94%) felt that a sound knowledge of anatomy helped them in their clinical term. However, more than 50% termed anatomy was difficult to understand and more than two-third agreed to the question that the duration of teaching anatomy should not be limited to one and a half year. Though 73% placed anatomy apart with clinical subjects. More than 80% compared teaching anatomy as favorable as treating a patient. In Bangladesh, lack of satisfactory job opportunities and adequate research facilities limits the uptake of anatomy as a career option. Even with a modified curriculum two third were willing to become an anatomist. A formal course in teaching was welcomed by most in case they sought to become anatomist. Key words: Anatomy; an emerging science; career option; students view. DOI: 10.3329/bja.v8i1.6106 Bangladesh Journal of Anatomy January 2010, Vol. 8 No. 1 pp. 28-33